Assessment of the Impact of Investments in Fixed Capital on the Economic Growth of the Northern Regions of the Russian Federation - A. Ts. Dolgunova (Статистика и экономика)
The purpose of the study. Despite the fact that a significant amount of research work has been accumulated on northern and Arctic topics, there is a lack of relevant research on the relationship between investments in fixed assets and economic growth for the northern regions of the Russian Federation. At the same time, northern regions are a special object of management: the specificity of the North breaks the usual ideas and patterns, making standard approaches to managing economic growth unacceptable or less effective. Currently, in the practice of strategic planning of investment activities in the North, there is a formal approach to the development of relevant documents: investment strategies are not always developed for a long-term period, they are generally not updated, the semantic content remains focused on the existing structure of production, the specifics of investment activity are not sufficiently reflected when setting goals regarding the natural and material characteristics of investment flows. The goal of the paper was to obtain quantitative estimates of the impact of capital investments on the economic growth of the northern region, which will allow a more reasonable approach to determining the values of target indexes and establishing the economic effect of planned investments.Materials and methods. For the northern regions of the Russian Federation, a retrospective analysis of the implementation of the relationship between the level of investment and incremental capital intensity (investment costs per unit of absolute growth in the gross regional product), as well as the level of investment and growth of the gross regional product, was carried out. An analysis of regional panel data from 12 northern regions of the Russian Federation was carried out to determine the influence of resource, investment, and innovation factors on the economic growth of the northern region.Results. High levels of economic dynamics in the northern region can only be achieved with a larger volume of investment compared to other regions of the country. Thus, an increase in gross regional product above 3% in a northern region is usually observed if the level of investment significantly exceeds the Russian average, i.e. is more than 30%. Based on the results of the panel analysis, estimates of the influence of investment and innovation factors on the economic growth of the northern region were obtained: an increase in the level of investment by 10 percentage points corresponds to an increase in the gross regional product of the northern region by 1.1%, an increase in the share of innovative goods, works, services by 10 percentage points corresponds to an increase in the gross regional product by 1.6%, an increase in the share of gross value added by the section of the AllRussian Classifier of Economic Activities “Extraction of Minerals” in the gross regional product by 10 percentage points corresponds to an increase in gross regional product of 6.7%.Conclusion. The economic growth of the northern region is significantly influenced by the degree of concentration of the economy on extraction of minerals. The innovative activity of enterprises and increased investment levels have a positive impact on regional economic dynamics. The positive effect that occurs when the level of investment in neighboring regions increases is also important. The presence of “northern value appreciation” continues to be a feature of investment processes in the North.